2017
DOI: 10.1063/1.4986132
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of the iso-thermal flow characteristics within a cylindrical chamber with multiple planar-symmetric impinging jets

Abstract: We present a joint experimental and numerical study of the flow structure within a cylindrical chamber generated by planar-symmetric isothermal jets, under conditions of relevance to a wide range of practical applications, including the Hybrid Solar Receiver Combustor (HSRC) technology. The HSRC features a cavity with a coverable aperture to allow it to be operated as either a combustion chamber or a solar receiver, with multiple burners to direct a flame into the chamber and a heat exchanger that absorbs the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The experimental studies of Boushaki and Sautet 4 employing Particle Image Velocimetry (PIV) showed that an increase in α j from 0 • to 30 • leads to a significant increase in the magnitude of mean and turbulent velocity fields within the jet merging region. Similarly, the PIV measurements of Long et al 10,11 found a strong dependence on jet angles (α j and θ j ) of the instantaneous and mean flow-fields generated with multiple symmetric jets. However, to the best of our knowledge, little or no information is available for the key geometrical parameters (e.g., L c and D c ) of the confined space for multiple jet configurations, although the aspect ratio of geometry has been found to have a significant influence on the flow-fields of free jet impingement [17][18][19] and cavity flow.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…The experimental studies of Boushaki and Sautet 4 employing Particle Image Velocimetry (PIV) showed that an increase in α j from 0 • to 30 • leads to a significant increase in the magnitude of mean and turbulent velocity fields within the jet merging region. Similarly, the PIV measurements of Long et al 10,11 found a strong dependence on jet angles (α j and θ j ) of the instantaneous and mean flow-fields generated with multiple symmetric jets. However, to the best of our knowledge, little or no information is available for the key geometrical parameters (e.g., L c and D c ) of the confined space for multiple jet configurations, although the aspect ratio of geometry has been found to have a significant influence on the flow-fields of free jet impingement [17][18][19] and cavity flow.…”
Section: Introductionmentioning
confidence: 64%
“…The present experimental arrangement is similar to that reported previously, 10,11 so only the key experimental apparatus and parameters are described here. Planar Particle Image Velocimetry (PIV) was employed to investigate the mean and RMS flow-fields with the MIJCC configurations.…”
Section: B Experimental Arrangementmentioning
confidence: 72%
See 3 more Smart Citations